Fiscal Decentralization and Environmental Pollution: A Spatial Analysis - Xia Chen; Jianmin Liu (Discrete Dynamics in Nature and Society)
Based on annual data over the period 2003 to 2017 covering 31 provinces in China, the environmental pollution index and environmental regulation index are constructed. Moran’s I, the widely used spatial autocorrelation index, is used to analyze the spatial distribution of environmental pollution, which provides a fairly high stability of the positive spatial correlation of environmental pollution. Then, the 0-1 matrix, distance weighting matrix, and economic distance mixed matrix are carried out to weigh space separately. To analyze the impact of fiscal decentralization on environmental pollution, the spatial Durbin model is employed. In the meanwhile, fiscal decentralization is measured from the perspective of both fiscal expenditure decentralization and fiscal revenue decentralization. The results show that the impact of fiscal decentralization on environmental pollution is positive and appears the phenomenon of “race to bottom.” To improve environmental quality, appropriate environmental regulation target, implementing green GDP accounting, and adjusting economic structure should be adopted.